Enabling easy and efficient hydrogen release below 80 °C from NaBH4 with multi-hydroxyl xylitol. (10th August 2021) - Zheng, Jiaguang; Liu, Meijia; Wu, Fuying; Zhang, Liuting
Abstract: NaBH4 has been widely considered as a low-cost hydrogen storage material with high gravimetric hydrogen capacity of about 10 wt%. However, its strong thermodynamic stability severely hinders the application of NaBH4 to obtain hydrogen. In this study, multi-hydroxyl xylitol, for the first time, was chosen as a protic hydrogen carrier to destabilize and react with NaBH4 . The NaBH4 -xylitol composites were easily prepared through hand-milling, which leads to the fast liberation of hydrogen from moderate temperatures lower than 80 °C with more than 3.6 wt% hydrogen desorption capacity. Besides, over 80% of hydrogen could be efficiently released in NaBH4 -xylitol composite. The dehydrogenation process is proved to be completely impurity-free and controllable by altering the NaBH4 /xylitol ratios and operating temperatures. The reaction between NaBH4 and xylitol is investigated to be similar to an alcoholysis procedure, however no observable liquid phase takes place before and after the dehydrogenation of NaBH4 -xylitol composite, showing a great potential to produce hydrogen under low temperatures through solid-state carriers. Highlights: A new strategy to use multi-hydroxyl xylitol to destabilize NaBH4 . NaBH4 -xylitol composite starts to release hydrogen before 80 °C with high efficiency. No observable liquid phase during dehydrogenation in NaBH4 -xylitol composite, showing high volumetric capacity.